2019
DOI: 10.1007/s11695-019-03830-7
|View full text |Cite
|
Sign up to set email alerts
|

The Safety and Benefits of Laparoscopic Sleeve Gastrectomy in Elderly Patients: a Case-Control Study

Abstract: Introduction The advancement of minimal invasive techniques pushed the age limit for patients qualified for bariatric surgery. Aim The aim of the study was to evaluate the safety and effectiveness of laparoscopic sleeve gastrectomy (LSG) in a cohort of patients aged 60 years or more, compared with a group of matched controls below 40 years old. Methods The medical records of 856 patients were analyzed. Patients aged 60 years or older were identified as cases. Those below 40 years were identified as the control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
1
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 25 publications
3
6
1
2
Order By: Relevance
“…In some studies on patients who underwent Bariatric surgery including sleeve gastrectomy (most common procedure), gastric bypasses, and gastric banding there was no significant difference in EWL between groups younger than 65 and over 65 years of age in 6, 12 and 24 months period of time (4,8). In some other reports, subjects over 45 showed less EBMIL after 12 months in comparison to younger group (7,9), which were in line with our results. This survey may have some limitations.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In some studies on patients who underwent Bariatric surgery including sleeve gastrectomy (most common procedure), gastric bypasses, and gastric banding there was no significant difference in EWL between groups younger than 65 and over 65 years of age in 6, 12 and 24 months period of time (4,8). In some other reports, subjects over 45 showed less EBMIL after 12 months in comparison to younger group (7,9), which were in line with our results. This survey may have some limitations.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies demonstrates that morbid obese subjects could lose up to 50 to 70 percent of excess weight or experience 25 to 35 percent body weight loss (6). Based on reports, older adults achieve weight loss same as younger ages but due to limited information on postoperative outcomes of laparoscopic sleeve gastrectomy, there is a general belief that all types of bariatric surgery is not good options for this population, while studies have illustrated that laparoscopic sleeve gastrectomy is a safe method for morbid obese subjects older than 60 years of age (7,8). When it comes to the relation of age and weight loss in bariatric surgery subjects, on the one hand, a former study reported that, adult morbid obese subjects over 45 demonstrated less excess BMI loss (EBMIL) after 12 months compared to younger group (9).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the last two decades, the popularity of bariatric surgery, especially SG, has increased dramatically worldwide 21 . Based on clinical studies, bariatric surgery is the most effective treatment for obesity 13,22 .…”
Section: Discussionmentioning
confidence: 99%
“…Algunos estudios iniciales sugieren que dicha eficacia puede ser menor que la lograda en pacientes jóvenes 15 , aunque la tasa de resolución general de las comorbilidades es aún superior que la lograda con el tratamiento médico, como se observó en el estudio de Bartosiak et al, donde la remisión de diabetes y de hipertensión, dos de los componentes del síndrome metabólico, fue significativa en el grupo de adultos mayores, con disminución de requerimiento de medicación y con impacto beneficioso en el aspecto socioeconómico. Si bien el descenso de peso fue mayor en pacientes más jóvenes, en los adultos mayores el mayor beneficio es la mejoría de las comorbilidades 16 .…”
Section: Discussionunclassified